Antibiofilm surface functionalization of catheters by magnesium fluoride nanoparticles - Lellouche J (Dove Medical Press, 2012)
Jonathan Lellouche1,2, Alexandra Friedman2, Roxanne Lahmi1, Aharon Gedanken2, Ehud Banin11The Mina and Everard Goodman Faculty of Life Sciences, 2The Kanbar Laboratory for Nanomaterials, Department of Chemistry, The Bar-Ilan Institute of Nanotechnology and Advanced Materials, Bar-Ilan University, Ramat-Gan, IsraelAbstract: The ability of bacteria to colonize catheters is a major cause of infection. In the current study, catheters were surface-modified with MgF2 nanoparticles (NPs) using a sonochemical synthesis protocol described previously. The one-step synthesis and coating procedure yielded a homogenous MgF2 NP layer on both the inside and outside of the catheter, as analyzed by high resolution scanning electron microscopy and energy dispersive spectroscopy. The coating thickness varied from approximately 750 nm to 1000 nm on the inner walls and from approximately 450 nm to approximately 580 nm for the outer wall. The coating consisted of spherical MgF2 NPs with an average diameter of approximately 25 nm. These MgF2 NP-modified catheters were investigated for their ability to restrict bacterial biofilm formation. Two bacterial strains most commonly associated with catheter infections, Escherichia coli and Staphylococcus aureus, were cultured in tryptic soy broth, artificial urine and human plasma on the modified catheters. The MgF2 NP-coated catheters were able to significantly reduce bacterial colonization for a period of 1 week compared to the uncoated control. Finally, the potential cytotoxicity of MgF2 NPs was also evaluated using human and mammalian cell lines and no significant reduction in the mitochondrial metabolism was observed. Taken together, our results indicate that the surface modification of catheters with MgF2 NPs can be effective in preventing bacterial colonization and can provide catheters with long-lasting self-sterilizing properties.Keywords: MgF2 NP coating, modified surfaces, bacterial colonization, human plasma, artificial urine, biocompatibility